2009
DOI: 10.1002/adfm.200801804
|View full text |Cite
|
Sign up to set email alerts
|

Surface‐Modified Mesoporous SiO2 Containers for Corrosion Protection

Abstract: The development of active corrosion protection systems for metallic substrates is an issue of prime importance for many industrial applications. The present work shows a new contribution to the design of a new protective system based on surface modified mesoporous silica containers. Incorporation of silica‐based containers into special sol–gel matrix allows for a self‐healing effect to be achieved during the corrosion process. The self‐healing ability occurs due to release of entrapped corrosion inhibitors in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
107
0
3

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 224 publications
(114 citation statements)
references
References 35 publications
4
107
0
3
Order By: Relevance
“…It is possible to deduce that dodecylamine load was in the range of a maximum of 13.4 wt.% (obtained from the difference of total mass loss in the presence and in the absence of dodecylamine from Tables 1 and 2) and a minimum of 12.2 wt.%, as discussed above. These estimates are reasonable and supported by other published papers Abdullayev et al, 2009;Fix et al, 2009;Skorb et al, 2009). Figure 2 shows the diffractograms for the samples of halloysite without and with treatment for 6 h in 2 mol/L sulfuric acid.…”
Section: Thermogravimetric Measurementssupporting
confidence: 90%
See 1 more Smart Citation
“…It is possible to deduce that dodecylamine load was in the range of a maximum of 13.4 wt.% (obtained from the difference of total mass loss in the presence and in the absence of dodecylamine from Tables 1 and 2) and a minimum of 12.2 wt.%, as discussed above. These estimates are reasonable and supported by other published papers Abdullayev et al, 2009;Fix et al, 2009;Skorb et al, 2009). Figure 2 shows the diffractograms for the samples of halloysite without and with treatment for 6 h in 2 mol/L sulfuric acid.…”
Section: Thermogravimetric Measurementssupporting
confidence: 90%
“…If 0.5% is discounted from the total (mass loss related to slope 3 in Figure 1A), 12.2% is obtained. This value makes sense, because in literature, a range of 5-10% of cargo is always reported for different nanocontainers Abdullayev et al, 2009;Fix et al, 2009;Skorb et al, 2009). These findings indicate that TGA technique is a good tool to estimate the inhibitor load in such inorganic nanocontainers.…”
Section: Thermogravimetric Measurementsmentioning
confidence: 99%
“…The similar corrosion inhibitor loaded halloysite nanotubes will be a promising candidate to generate self-healing anticorrosive epoxy protective coating for metals. Mesoporous silica was also used to load corrosion inhibitors for sol-gel protective coating for metal [79]. Maia et al [80] adopted a one step process including synthesis of silica nanocapsules (SiNC) and loading of corrosion inhibitor 2-mercaptobenzothiazole (MBT) which outlook the mass production.…”
Section: Inorganic Nanomaterials As Self-healing Agent Containersmentioning
confidence: 99%
“…In order to avoid spontaneous delivery, encapsulation of loaded mesoporous nanoparticles is also helpful [9]. Among the possible different technologies for encapsulation, the Layer-by-Layer (LbL) deposition technology of oppositely charged species (polyelectrolytes, nanoparticles, enzymes, dendrimers, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…To date, despite the great number of studies carried out worldwide and although some alternatives have shown good behaviour in certain conditions, no definitive solution has been found for the replacement of chromates by nontoxic pigments. Recent developments in surface science and technology open up new opportunities through the integration of nanoscale containers (carriers) loaded with active components into coatings [8][9][10][11][12]. Suitable nanoparticle design would allow the controlled release of the inhibitor in response to external stimuli (change in pH, temperature, physical breakage of paint film, etc.…”
Section: Introductionmentioning
confidence: 99%